GRAVITY MODEL ON A SINGLE COMMODITY: A REVIEW OF LITERATURE - Ming, Lee Siu; Adam, Radziah; Tuan Lonik, Ku’Azam (Management Research Journal, 2016)
Gravity model when applied on specific commodities offer novelty in terms of findings of the demand and supply factors of the specific commodities which are different from the aggregated trade flows. This article provides an extensive systematic review of the literature on the gravity model of trade on single commodities and highlights the research gap that exists for further research. The ‘commodity-specific gravity model’ is the pioneering model incorporating the characteristics closely related to the specific commodity studied. A significant number of studies of gravity model of specific commodities are focused on primary products, and the scope should be expanded to products in the secondary sector of economy. It is our view that the model can be used to examine the effects of free trade agreements, which may provide suggestion of beneficial trade policies for exporting and importing countries. Future studies can also explore on the methodological aspect of the gravity model, which is still relatively scarce.